Pengaruh Pijat Perineum terhadap Laserasi Perineum pada Ibu Bersalin - Villa Yulinar S; Shinta Novelia; Rumaini Rukmaini (Jurnal Akademika Baiturrahim Jambi, 2023)
Perineal laceration will cause bleeding during delivery, causing maternal death. A stiff perineum is an indication for an episiotomy. The occurrence of a very broad perineum can cause heavy bleeding in the mother during childbirth. Destination this study aims to determine the effect of perineal massage on perineal lacerations in women giving birth between the experimental group and the control group at the Sindang Jaya Public Health Center. This quasi-experimental research uses an Experiment and Control Group design. The population in this study were pregnant women in the third trimester with gestational age <34 weeks. The research instrument consisted of a checklist and a partograph as a measuring tool. Data were analyzed using normality test. Result a P Value of 0.000 (<0.05) meaning that there was a significant difference between lacerations in the experimental group and the control group.Conclusions and recommendation is perineal massage for pregnant womenable to prevent perineal laceration during labor. This perineal massage can be applied in private midwifery practices or carried out by patients themselves at home regardless of parity.